Breaking up is hard to do : ASEAN and the South China Sea - Chong, Alan (2013)
Facetious suggestions that ASEAN should be reduced to a 'League of South China Sea Nations' in the wake of the recent brouhaha over maritime territorial disputes ignore Southeast Asia's unique brand of multilateralism.